MOTIVATION FOR LEARNING SPEAKING SKILLS USING VIDEO BLOG (VLOGGING) BASED ON PROJECT LEARNING STUDENTS OF THE INDONESIAN LANGUAGE AND LITERATURE EDUCATION DEPARTMENT AT NUSA CENDANA UNIVERSITY: A PHENOMENOLOGY APPROACH - Yakobus M. Langkelang Niron (IJLECR (International Journal of Language Education and Cultural Review), 2020)
This study aims to identified students motivation in learning project-based learning (PBL) Indonesian language skills using vlogging media based on meanings and themes seen from the "because motives" and "in order to motives" related to the phenomenon of learning in the classroom. In identifying objectives, this study uses a qualitative research method with the approach of phenomenology from Albert Schutz's perspective. Researcher becomes the main instrument in an effort to obtain and find data. The research subjects were 38 second semester students of the Department of Language and Literature at Nusa Cendana University. Data collection techniques used include observation, questionnaires, and interviews. Data analysis through three stages of the flow model namely reduction, presentation and verification of data and triangulation. The results of the study prove that the teaching strategy associated with vlogs can attract students' learning interest because of their interest in other fields such as multimedia technology and social media. The application of learning PBL-based speaking skills using vlogs can improve speaking competence and gradually improve the mental aspects of students to become more confident to speak and communicate in public. So it can be said that learning PBL-based speaking skills using vlogs is a good and innovative learning strategy in an effort to increase learning motivation and mastery of students' speaking skills.